GENDER AND ITS ROLES: WOMEN IN BUSINESS LIFE OF TURKEY - SARIBAŞ, Serap (Atlas Journal, 2022)
When the business life of women is examined in the historical process, it changes depending on factors such as production and industrialization, especially the social and cultural areas of the society in which she lives. Discriminatory approach policies can be traced back to prehistoric times. People are thought to have adopted cave life and instinctively divided labor during the Paleolithic period. This division of labor defined as Hunter-Gatherer is interpreted as men living a hunter-gatherer lifestyle and women living a gatherer lifestyle. It can be interpreted that biological power differences lie on the basis of the discrimination policy. This discrimination policy, based on biological differences, took on new dimensions with the transition to settled life, agriculture, and, finally, the industrial revolution, and women came to be viewed as an element of exploitation within the system over time. The aim of this study is to evaluate the place of women in the business life in Turkey in the light of scientific data, based on the concept of gender and its formation.